Experimental and numerical investigation of nanomaterial-based structural composite - Kanif Markad; Vivek Patekar; Kishor Kale (Curved and Layered Structures, 2024)
In this work, we discussed multi-phase composites fabrication and analytical as well as experimental analysis. Shear mixing of multi-walled nanotube (MWCNT) and epoxy is used to create nanocomposites. Ultrasonication, magnetic stirring, and moulding using the hand layup technique were the procedures used for sample preparation. Curing and cutting were performed as well, all in accordance with ASTM standards. This research uses an experimental method for assessing material qualities and backs up its findings with an analytical one for verification. It can be shown that the outcomes of both experiments and analyses are consistent. The structural analysis of a composite sample is probed by using a further analytical validation strategy. In this research, we examined the effects of varying the MWCNT content of the matrix. The tensile strength was shown to rise up to 0.5% MWCNT content in the matrix. For 0.7% MWCNT reinforcement in the matrix, tensile strength drops as a result of agglomeration. This research also explored the use of ANSYS for critical buckling analysis on many different multi-phase nanocomposite samples. The critical buckling resistance capability of the various configurations of composite materials was examined, and the model’s efficacy was shown via validation against existing literature.